Confucian relationism and global ethics: alternative models of ethics and axiology in times of global crises - Rošker, Jana S. (East Asian comparative literature and culture, 2023)
Prologue: The year of the Metal Rat, the curse of the Bat and the search for a new ethos -- Methodological introduction -- Freedom, responsibility and the relationship between the individual and society -- Confucian humanism and democracy -- Subjectivity, control, and digital technology -- Restructuring the axiology of global ethics: On a winding path from transcultural to global ethics -- Epilogue: The new politeia, the land of rusting arms, and the deliverance from dark times.